Thinking through graphic design history : challenging the canon. - Toppins, Aggie (London : Bloomsbury Publishing Plc, 2025)
Graphic design has a paradoxical relationship to history. While it claims to promote originality and innovation - ideas that emphasize the new and unique - design practice is deeply embedded in previous ideals. Too often, design students encounter the past in brief visual impressions which seduce them to imitate form rather than engage with historical contexts. Even though it has claimed to be objective and even comprehensive, graphic design history has focused largely on individual careers and Eurocentric achievements.Yet the past swells with untapped potential. Graphic design history can serve the field of today and tomorrow, but its narratives require updates. History, like design, is always changing - and like design, history is driven by present-day questions. This book shows how students and practicing designers can enrich their work by thinking historically about design. With thoughtful analyses, stimulating creative prompts, inspiring case studies, and perspectives from designers all over the world, this book challenges our traditional understanding of graphic design history, and the very notion of the design canon, offering ways to shape socially engaged, critical practices.
boek